2018
DOI: 10.5194/nhess-2018-126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating critical rainfall conditions for large-scale landslides by detecting event times from seismic records

Abstract: Abstract.One of the purposes of slope disaster research is to establish an early warning method for rainfall-induced landslides. The insufficient observational records of the past, however, have inhibited the analysis of critical rainfall conditions. This dilemma may be resolved by extracting the times of landslide occurrences from the seismic signals recorded by adjacent seismic stations. In this study, the seismic records of the

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…
Zhou et al, 2019). The distribution pattern of LSL shows close relation to the seismic fault/thrust Li, 2008, 2009) and most of the LSL are found to be oriented perpendicular to direction of the regional thrust system and proximity to the fault/thrust system (Timilsina et al, 2012; Zhou et al, 2019).The effects of rainfall duration and cumulated rainfall are much more remarkable for LSL than for small landslides (Kuo et al, 2018). The major factors that affect the distribution of LSL triggered by the seismic event are distance effect, locked segment effect, hanging wall effect and direction effect (Xu et al, 2011).
…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…
Zhou et al, 2019). The distribution pattern of LSL shows close relation to the seismic fault/thrust Li, 2008, 2009) and most of the LSL are found to be oriented perpendicular to direction of the regional thrust system and proximity to the fault/thrust system (Timilsina et al, 2012; Zhou et al, 2019).The effects of rainfall duration and cumulated rainfall are much more remarkable for LSL than for small landslides (Kuo et al, 2018). The major factors that affect the distribution of LSL triggered by the seismic event are distance effect, locked segment effect, hanging wall effect and direction effect (Xu et al, 2011).
…”
mentioning
confidence: 91%
“…Landslides often classified based on factors; materials, landslide scale, or type of movement (Varnes, 1978;Cruden and Varnes, 1996;Hungr et al, 2014). The size of landslide larger than 10 5 m 2 is commonly accepted to be large-scale landslides (Wen and Chen, 2007;Lin et al, 2013;Zhou and Cheng, 2015) and volume larger than 10 6 m 3 (Brueckl and Parotidis, 2001;Zerathe et al, 2014;Chung et al, 2018;Kuo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Tijuana metropolitan area, rotational soil slides are the most common landslide type and abrupt events have been recognized as a significant threat to public safety (Oliva-González et al, 2014). Landslides occur when the weight of earth material down a slope exceeds its strength (Highland and Bobrowsky, 2008), a process known as overloading that typically occurs with high soil moisture content following rainfall (Kuo et al, 2018;Valenzuela et al, 2018;Zhuo et al, 2019;Monsieurs et al, 2019;Marino et al, 2020) or agricultural intensification (Lacroix et al, 2020). Recent studies have also shown that leaky pipes and septic tanks contribute to overloading (Demoulin and Hans-Balder, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce losses caused by landslides, it is necessary to identify critical rainfall that can trigger landslides, so that rainfall threshold is obtained as an approximate model for disaster prevention and mitigation (Kuo et al, 2018). The difficulty in estimating rainfall threshold is the lack of accurate information.…”
Section: Introductionmentioning
confidence: 99%